Evaluation of Narrow Band Ultraviolet B (NBUVB) Treatment in Patients with Lichen Planus - Farah Saleh Abdul-Reda (Journal of Global Pharma Technology, 2016)
Background: In lichen planus, cutaneous lesions usually resolve within 2 years; however, treatment may be justified to reduce time till resolution and relieve the symptom of itching. Treatment may include a variety of agents that have been described as 1st line, second line and third line therapies. Oral lesions may resolve spontaneously within 5 years; but most cases are chronic, therefore treatment must be justified when ulcerative lesions interfere with normal feeding, otherwise treatment should be avoided because the burden of side effects is much more than the obtained benefit.  Aim of the study: to evaluate the response of patients with lichen planus to narrow band ultraviolet B phototherapy. Patients and methods: The present cohort study included 40 patients with lichen planus with and age range of 11 to 55. The study was carried out at the dermatology unit, Al-Diwaniyah Teaching Hospital located at Al-Diwaniyah province, Mid-Euphrates region of Iraq. The duration of study extended from January 2018 till March 2019.All patients were treated twice weekly (two sessions per a week).The starting dose was 150-200 mj/cm2, then the dose was increased 10-20% per session. All patients were followed for a period of 6 up to 12 months in order to record the quality of response and relapse and number of relapses if ever happened. Results: Patients received treatment sessions that ranged from 25 up to 50. Patients with excellent response accounted for 20 (50 %), patients with good response accounted for 10 (25 %), patients with fair response accounted for 7 (17.5 %) and patients with poor response accounted for 3 (7.5 %). Response to treatment showed no correlation to any of demographic characteristics. After 6 months of follow up only 5 patients developed relapse and after one year the number rises to 7 patients. Conclusion: In view of the available data obtained from the current study and previous reports it is obvious that NBUVB treatment in patients with lichen planus is associated with an acceptable complete and partial response rate with good patient satisfaction.Keywords: Lichen planus, Narrow band ultraviolet B therapy.